Gastrointestinal Polyposis in Pediatric Patients. Issue 3 (September 2019) - MacFarland, Suzanne P.; Zelley, Kristin; Katona, Bryson W.; Wilkins, Benjamin J.; Brodeur, Garrett M.; Mamula, Petar
Abstract : ABSTRACT: Gastrointestinal polyps are mucosal overgrowths that, if unchecked, can undergo malignant transformation. Although relatively uncommon in the pediatric age group, they can be the harbingers of multiorgan cancer risk and require close management and follow-up. Additionally, as many polyposis syndromes are inherited, appropriate genetic testing and management of relatives is vital for the health of the entire family. In this review, we discuss both common and uncommon childhood gastrointestinal polyposis syndromes in terms of clinical presentation, management, and surveillance. We also detail any additional malignancy risk and surveillance required in the pediatric age group (<21 years old). Through this review, we provide a framework for gastroenterologists to manage the multifaceted nature of pediatric polyposis syndromes.